Program Kelompok Pengenalan Kegawatdaruratan Dasar (KOPDAR) Sebagai Upaya Penanganan Pertama Cedera Ekstremitas Di Sekolah Di Sekolah - Eky Madyaning Nastiti; Feri Ekaprasetia; Rida Darotin (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Extremity injuries are often found in everyday events around us. School children are an age group that is vulnerable to injury due to curiosity about things around them. For this reason, it is important to make efforts to increase the knowledge of school residents, especially students in preventing limb injuries. The purpose of this community service is to introduce the concept of handling cases of extremity injuries that often occur in schools. The methods used in this activity are lectures, demonstrations and discussions using poster media. The target of this activity was class VIII students located at SMPN 12 Jember which was carried out during September 2022. The result of this activity was that after implementation it was obtained that data on participants' understanding of the concept of handling limb injuries was classified as sufficient as much as 25% and 75% were classified as good. There is an increase in students' understanding in handling limb injuries by having confidence and being able to provide treatment in these cases by using the Rest, Ice, Compression and Elevation methods.